DERIVATIVE POSSIBILITIES OF LEXEMES IN TURKISH AND UZBEK LANGUAGES IN LINGUISTIC DATABASE - Madina Shukhrat qizi, Norbekova (Journal of Ethics and Diversity in International Communication, 2021)
Among all the fields that are developing in the age of technology, automatic translation of languages (machine translation) is also developing. Automatic translation requires the translation of compound words, phrases, and separate coding and classification of words. Translation of stable compounds in Uzbek and Turkish is easier than in Uzbek-English.